Mitochondrial Dysfunction in Neonatal Hypoglycemia: Mechanistic Insights and Therapeutic Targets - MHM, Nazmul; Shwe, Wana Hla; Moftah, Abdulhameed Gadmor; Udayah, Manglesh Waran; Gupalo, Sergey; Saghir, Fatma SA; Y, Farzana; Doustjalali, Saeid Reza; Sabet, Negar Shafiei; Oo, Khin Thane; et al. (Journal of Neonatal Surgery, 2025)
Neonatal hypoglycemia is a critical metabolic condition that can severely impair brain development, with mounting evidence pointing to mitochondrial dysfunction as a central mechanism of injury. This study investigates the bioenergetic and structural consequences of hypoglycemia-induced mitochondrial damage in neonatal rats and evaluates the efficacy of mitochondria-targeted therapies. Following insulin-induced hypoglycemia in postnatal day-7 pups, significant reductions in ATP levels (45.3%, p <0.01), oxidative phosphorylation complex I and III activity (39.8% and 33.4%, respectively), and mitochondrial membrane potential (50% loss in JC-1 red/green ratio) were observed. Concurrently, ROS levels increased 2.7-fold and lipid peroxidation rose by 65.2%, accompanied by elevated markers of apoptosis (cytochrome c, caspase-9) and inflammation (NLRP3, TNF-α). Treatment with MitoQ and SS-31 restored ATP levels to over 80% of baseline, reduced ROS by 40%, and suppressed caspase-9 activation by 55%, highlighting the therapeutic potential of targeting mitochondrial pathways. These findings provide mechanistic insight into how neonatal hypoglycemia disrupts mitochondrial homeostasis and demonstrate that early pharmacological intervention can mitigate ensuing neurodegenerative cascades.